ANALISIS STRATEGI PENGEMBANGAN EKOWISATA AIR TERJUN RIAM BEGIHAM DESA BUNGKANG KECAMATAN SEKAYAM KABUPATEN SANGGAU - Godut, Chrystina Ellia; Padmarsari2, FX Widadi; Hadinata, Fitra Wira (Fakultas Pertanian Universitas Tanjungpura, 2024)
Sanggau Regency has ecotourism potential, one of which is the Riam Begiham Waterfall, located in Bungkang Village, Sekayam District. Research on the Riam Begiham Waterfall has been studied by previous researchers, however, it has not yet produced a strategy for developing the Riam Begiham Waterfall. Therefore, the researcher intends to carry out an analysis of ecotourism development strategies at Riam Begiham Waterfall, with the aim of knowing the internal and external factors that exist at Riam Begiham Waterfall and making an appropriate development strategy plan for ecotourism development at Riam Begiham Waterfall. This research was carried out during the month September-October 2024 at Riam Begiham Waterfall, Sekayam District, Sanggau Regency. The data taken is in the form of internal and external factors, then data analysis is carried out to find out internal and external factors and the right strategy for developing Riam Begiham Waterfall. Based on the results of the analysis of internal and external factors, it was found that the position of Riam Begiham Waterfall is in quadrant I, which means there is significant strategic potential for the development of Riam Begiham Waterfall. The strategy that can be proposed is Strength- Opportunity (SO).